2010
DOI: 10.1128/aem.01679-09
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Host-Range Plasmids for Red Fluorescent Protein Labeling of Gram-Negative Bacteria for Use in the Zebrafish Model System

Abstract: To observe real-time interactions between green fluorescent protein-labeled immune cells and invading bacteria in the zebrafish (Danio rerio), a series of plasmids was constructed for the red fluorescent protein (RFP) labeling of a variety of fish and human pathogens. The aim of this study was to create a collection of plasmids that would express RFP pigments both constitutively and under tac promoter regulation and that would be nontoxic and broadly transmissible to a variety of Gram-negative bacteria. DNA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…A red fluorescent protein-expressing derivative of Pseudomonas aeruginosa clinical isolate strain PA14 (PA14-dTom [80]) or the PA14-derived ΔlasR (16), transformed with the same plasmid, was grown on LB media (10 g/liter Bacto tryptone, 5 g/liter Bacto yeast extract, 10 g/liter sodium chloride, 1.2% agar; BD, San Jose, CA) supplemented with 750 g/ml ampicillin (EMD Millipore, Billerica, MA) overnight at 37°C. For infections, liquid cultures of P. aeruginosa were grown by rotating overnight in LB-Amp (750 g/ml) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…A red fluorescent protein-expressing derivative of Pseudomonas aeruginosa clinical isolate strain PA14 (PA14-dTom [80]) or the PA14-derived ΔlasR (16), transformed with the same plasmid, was grown on LB media (10 g/liter Bacto tryptone, 5 g/liter Bacto yeast extract, 10 g/liter sodium chloride, 1.2% agar; BD, San Jose, CA) supplemented with 750 g/ml ampicillin (EMD Millipore, Billerica, MA) overnight at 37°C. For infections, liquid cultures of P. aeruginosa were grown by rotating overnight in LB-Amp (750 g/ml) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…P. aeruginosa(p67T1), which constitutively expresses the fluorescent protein dTomato, was incubated overnight in LB broth containing ampicillin at a concentration of 750 g/ml (30). Cultures were spun at 2,450 ϫ g for 5 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type nonmucoid P. aeruginosa strains PA14, PA14 ⌬LasR, and PA14 ⌬T3SS were generously provided by George A. O'Toole and Deborah A. Hogan (Dartmouth Medical School, Hanover, NH). Strain PA14(p67T1) was constructed recently (51) and carries a constitutive plasmid-encoded red fluorescent protein (RFP) variant of d-Tomato that was engineered by Shaner et al (49). A P. aeruginosa CF lung isolate designated SMC573 was provided by Joe Schwartzman (Dartmouth-Hitchcock Medical Center, Lebanon, NH).…”
Section: Methodsmentioning
confidence: 99%
“…4c and d). We have previously shown that RFP-expressing and wild-type strains of P. aeruginosa are equally virulent and that the production of RFP has no effect on bacterial burden (51). Increased bacterial burden is unique to P. aeruginosa.…”
Section: Assessment Of P Aeruginosa Infection By Microinjection Pmentioning
confidence: 99%